Voleibol infanto-juvenil brasileiro: Somatotipia, qualidades físicas e marcadores genéticos dos atletas em diferentes níveis de qualificação esportiva - Cabral, Breno Guilherme de Araújo Tinôco (2007)
The elaboration of profiles with characteristics that can be parameters in the different categories of sports modalities and the investment in scientific studies have revealed a significant importance in the development of new generations of athletes. Based in the exposed, the purpose of this study was to identify and compare the somatotype characteristics, physical qualities and genetic markers of Brazilian male volleyball players in the 14-17 category playing at different levels (international, national and regional). We used a scale, stadiometer, pachymeter, and adipometer to evaluate somatotype, attack and block reach test, medicine ball toss, 30-meter agility test , the AAHPER -30 test to evaluate basic physical qualities and the dermatoglyphic method to identify genetic markers. The results show the superiority of the national team over the other squads in the somatotype component (ectomorphy), and in the level of basic physical qualities. We found no significant difference in genetic markers among the teams studied. We conclude that Brazilian volleyball players at different performance levels have characteristics peculiar to the sport, with height and physical qualities being significantly different among these teams. The results confirm de necessity of knowing the athletes specific characteristics when dealing with high performance teams using nutrition, medicine, physiology and genetics specific knowledges to achieve a better sportive development